Microeconomics and behavior - Frank, Robert H., 1945- (McGraw-Hill Education, 2015)
"Robert Frank's Microeconomics and Behavior covers the essential topics of microeconomics while exploring the relationship between economic analysis and human behavior. Core analytical tools are embedded in a uniquely diverse collection of examples and applications to illuminate the power and versatility of the economic way of thinking. Students are encouraged to become "Economic Naturalists" who see the mundane details of ordinary existence in a sharp new light"-- Resumé vydavatele